"Smart" nanosensors for early detection of corrosion: Environmental behavior and effects on marine organisms. (1st June 2022) - Martins, Roberto; Figueiredo, Joana; Sushkova, Alesia; Wilhelm, Manon; Tedim, João; Loureiro, Susana
Abstract: Corrosion is an environmental and economic global problem. "Smart" or stimuli-responsive colorimetric nanosensors for maritime coatings have been proposed as an asset to overcome the limitations of the current monitoring techniques by changing color in the presence of triggers associated with the early stages of corrosion. Layered double hydroxides (Zn–Al LDH; Mg–Al LDH) and silica mesoporous nanocapsules (SiNC) were used as precursor nanocarriers of active compounds: hexacyanoferrate ions ([Fe(CN)6 ] 3- ) and phenolphthalein (PhPh), respectively. Additionally, the safer-by-design principles were employed to optimize the nanosensors in an eco-friendly perspective (e.g., regular vs. warm-washed SiNC-PhPh; immobilization using different carriers: Zn–Al LDH-[Fe(CN)6 ] 3- vs. Mg–Al LDH-[Fe(CN)6 ] 3- ). Therefore, the present study aims to assess the environmental behavior in saltwater and the toxic effects of the nanosensors, their nanocarriers, and the active compounds on the marine microalgae Tetraselmis chuii and the crustacean Artemia salina . Briefly, tested compounds exhibited no acute toxic effects towards A. salina (NOEC = 100 mg/L), apart from SiNC-PhPh (LC50  = 2.96 mg/L) while tested active compounds and nanosensors caused significant growth inhibition on T. chuii (lowest IC50  = 0.40 mg/L for SiNC-PhPh). The effects of [Fe(CN)6 ] 3- were similar regardless of the nanocarrier choice. Regarding SiNC-PhPh, its toxicity can be decreased at least twice by simply reinforcing the nanocapsules washing, which contributes to the removal (at least partially) of the surfactants residues. Thus, implementing safe-by-design strategies in the early stages of research proved to be critical, although further progress is still needed towards the development of truly eco-friendly nanosensors. Graphical abstract: Image 1 Highlights: Nanostructured colorimetric sensors can be used for early detection of corrosion. Nanosensors are unstable and tend to aggregate in low and ionic strength medium. Zn–Al/Mg–Al LDH-[FeCN6 ] 3- were less toxic than SiNC-PhPh towards tested species. Safer-by-design improvements can decrease the toxicity of innovative nanosensors.